What is true and what is new in esophageal microbiome in 2024? - M. Jauvain; E. Bessède (Microbiota in Health and Disease)
Research on the esophageal microbiome is a relatively new field. While the microbiota in the lower tract of the intestine, namely the small and large bowel, has been the core of scientific interest over the last 20 years, the resident microbial flora of the esophagus and its potential role in the pathogenesis of esophageal diseases have been neglected. The esophageal microbiota refers to the dynamic community of microorganisms that inhabit the esophagus, influenced by several factors, including diet, age, and diseases, and it is proposed to play a role in several esophageal disorders, including eosinophilic esophagitis (EoE), gastroesophageal reflux disease (GERD), esophageal carcinomas and carcinogenesis, and achalasia. This review will outline data from studies published in the past year, mainly focusing on esophageal cancer and motility disorders, characterizing the esophageal microbiome in both health and disease states.